"Smart Living": Telecentre as the Basis for A Sustainable Rural Economy in Malaysia - Faeeq, Munadil Khaleel; Abdul Rahim, Noor Fareen (2016)
This research explains successful and economic sustainability model of information technology awareness in rural areas among Malaysian users. In general, we review the literature found three models in three countries (India, Brazil, and Taiwan). These countries are trying to develop a sustainable Smart Living project by establishing information system in rural areas among Malaysian users. This study explains and propose new successful sustainability and economic model in Malaysia to establish Information Technology (IT) in Malaysia. The main objective is to create a sustainable publishing Smart Living project in Malaysia. Moreover, there is scarcity of the research that consider the long term sustainability of technology projects. Finally, it aims to overcome the challenges and issues in different countries, and get benefit 6om their experiences in overcoming the problems and barriers that may face in applying sustainable and economic model of Smart Living project in Malaysia or other counties that currently did not used Smart Living project.